2016
DOI: 10.1152/ajpcell.00148.2015
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of uncoupling protein 2 in GLP-1-producing cells after chronic high glucose exposure: implications for the pathogenesis of diabetes mellitus

Abstract: Glucagon-like peptide-1 (GLP-1) is a gut L-cell hormone that enhances glucose-stimulated insulin secretion. Several approaches that prevent GLP-1 degradation or activate the GLP-1 receptor are being used to treat type 2 diabetes mellitus (T2DM) patients. In T2DM, GLP-1 secretion has been suggested to be impaired, and this defect appears to be a consequence rather than a cause of impaired glucose homeostasis. However, although defective GLP-1 secretion has been correlated with insulin resistance, little is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…We also investigated the effects of these peptides on UCP2 expression in hippocampal NSCs exposed to HG. In agreement with previous studies demonstrating increased UCP2 activity in response to hyperglycemia (Koziel et al 2015, Urbano et al 2016, we found that UCP2 protein levels were significantly increased by HG. Enhanced activity of UCP2 in hyperglycemic condition is known to lessen the reduction level of mitochondrial respiratory chain complexes and result in the attenuation of mitochondrial ROS production (Koziel et al 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also investigated the effects of these peptides on UCP2 expression in hippocampal NSCs exposed to HG. In agreement with previous studies demonstrating increased UCP2 activity in response to hyperglycemia (Koziel et al 2015, Urbano et al 2016, we found that UCP2 protein levels were significantly increased by HG. Enhanced activity of UCP2 in hyperglycemic condition is known to lessen the reduction level of mitochondrial respiratory chain complexes and result in the attenuation of mitochondrial ROS production (Koziel et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that HG exposure induces significant upregulation of UCP2 (Koziel et al 2015, Urbano et al 2016). Similar to these findings, we found that HG exposure significantly increased UCP2 expression in a time-dependent manner ( Fig.…”
Section: Ampk/ucp2 Pathway Mediates Anti-apoptotic Effects Of Ghrelinmentioning
confidence: 99%
“…For Western blot analysis, cell lysates were analyzed as previously described (38). Proteins of interest were detected with the following specific antibodies: antiphospho-IRS-1 (Tyr612) and anti-total IRS-1 (Santa Cruz Biotechnology); anti-phospho-AKT (Ser473) and anti-total AKT (Cell Signaling Technology); anti β-Actin (Sigma-Aldrich).…”
Section: Cell Lysis Immunoprecipitation and Western Blot Analysis Inmentioning
confidence: 99%
“…UCP1 is a potential target for the treatment of patients with diabetes and improves the whole metabolism . In addition, the altered expression of UCP2 is implicated in the pathogenesis of diabetes, and the activation of UCP2 in diabetic mitochondria seems to be a response to the diabetes process that leads to more efficient cleaving of ROS . Of interest, the upregulation of UCPs has been observed in several MR models, indicating a potential mechanism in MR‐mediated mitochondrial respiratory chain.…”
Section: Mr and Diabetesmentioning
confidence: 99%